The Roles of Noncoding RNAs in Systemic Sclerosis - Liu, Yongmei; Cheng, Linlin; Zhan, Haoting; Li, Haolong; Li, Xiaomeng; Huang, Yuan; Li, Yongzhe (Frontiers in Immunology, 2022)
Noncoding RNAs (ncRNAs) constitute more than 90% of the RNAs in the human genome. In the past decades, studies have changed our perception of ncRNAs from “junk” transcriptional products to functional regulatory molecules that mediate critical processes, including chromosomal modifications, mRNA splicing and stability, and translation, as well as key signaling pathways. Emerging evidence suggests that ncRNAs are abnormally expressed in not only cancer but also autoimmune diseases, such as systemic sclerosis (SSc), and may serve as novel biomarkers and therapeutic targets for the diagnosis and treatment of SSc. However, the functions and underlying mechanisms of ncRNAs in SSc remain incompletely understood. In this review, we discuss the current findings on the biogenetic processes and functions of ncRNAs, including microRNAs and long noncoding RNAs, as well as explore emerging ncRNA-based diagnostics and therapies for SSc.